(x+12)(x-1)=2(x-6)-20

Simple and best practice solution for (x+12)(x-1)=2(x-6)-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+12)(x-1)=2(x-6)-20 equation:


Simplifying
(x + 12)(x + -1) = 2(x + -6) + -20

Reorder the terms:
(12 + x)(x + -1) = 2(x + -6) + -20

Reorder the terms:
(12 + x)(-1 + x) = 2(x + -6) + -20

Multiply (12 + x) * (-1 + x)
(12(-1 + x) + x(-1 + x)) = 2(x + -6) + -20
((-1 * 12 + x * 12) + x(-1 + x)) = 2(x + -6) + -20
((-12 + 12x) + x(-1 + x)) = 2(x + -6) + -20
(-12 + 12x + (-1 * x + x * x)) = 2(x + -6) + -20
(-12 + 12x + (-1x + x2)) = 2(x + -6) + -20

Combine like terms: 12x + -1x = 11x
(-12 + 11x + x2) = 2(x + -6) + -20

Reorder the terms:
-12 + 11x + x2 = 2(-6 + x) + -20
-12 + 11x + x2 = (-6 * 2 + x * 2) + -20
-12 + 11x + x2 = (-12 + 2x) + -20

Reorder the terms:
-12 + 11x + x2 = -12 + -20 + 2x

Combine like terms: -12 + -20 = -32
-12 + 11x + x2 = -32 + 2x

Solving
-12 + 11x + x2 = -32 + 2x

Solving for variable 'x'.

Reorder the terms:
-12 + 32 + 11x + -2x + x2 = -32 + 2x + 32 + -2x

Combine like terms: -12 + 32 = 20
20 + 11x + -2x + x2 = -32 + 2x + 32 + -2x

Combine like terms: 11x + -2x = 9x
20 + 9x + x2 = -32 + 2x + 32 + -2x

Reorder the terms:
20 + 9x + x2 = -32 + 32 + 2x + -2x

Combine like terms: -32 + 32 = 0
20 + 9x + x2 = 0 + 2x + -2x
20 + 9x + x2 = 2x + -2x

Combine like terms: 2x + -2x = 0
20 + 9x + x2 = 0

Factor a trinomial.
(5 + x)(4 + x) = 0

Subproblem 1

Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5

Subproblem 2

Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4

Solution

x = {-5, -4}

See similar equations:

| 6x+3*(-3)=9 | | 6x-1/2=9 | | -7.8x+2.4x=40 | | -4+4X=-16+13 | | 6*2+3y=9 | | 2x-5+4x+10=21 | | 24x^3+8x^2=100x^2+-28x | | -2(-4-3x)=-28 | | 6x+1=12-2x | | 7*log(3x)+3log(5x)=15 | | 20+9b=38 | | 7x-11+9=180 | | 18+3x=24+2x | | 3y+45=90 | | 1/2x-4=7/3 | | 12x+375=639 | | 0.6x+120=0.68x-448 | | 15/7-5/14 | | 12xy-xy= | | 375x+20=639 | | Sin30/10 | | 5x^2-4=41 | | 375+12c=630 | | 7X-2=8X+11 | | 8(v+7)-5= | | tanx=0.2222222 | | 2r+8=12r+13 | | Cos*x=0.59 | | x-11=-38 | | 2x-4x+21=4x+39 | | 0.4(2x+4)=0.3x+6 | | 6(2p-3)+p= |

Equations solver categories